Catheter ablation and cognitive function in atrial fibrillation: A systematic review and meta-analysis - Chen, Pengfei; Chen, Zhuhong; Pan, Deng; Miao, Lina; Shi, Yujiao; Guo, Ming; Du, Jianpeng (Frontiers in Neurology, 2022)
Background Atrial fibrillation (AF) is a risk factor for cognitive dysfunction. Although catheter ablation (CA) is one of the main treatments for AF, whether it can improve cognitive function in patients with AF remains unclear. We conducted a systematic review and meta-analysis to evaluate the cognitive outcome post-CA procedure. Methods Two investigators independently searched the PubMed, EMBASE, Web of Science, CNKI, WanFang, and VIP databases from inception to September 2021 for all the potentially eligible studies. The outcomes of interest included dementia or cognitive disorder through scoring or recognized classification criteria. Heterogeneity was determined by using Cochrane's Q test and calculating the I2. A random-effects model was used to incorporate the potential effects of heterogeneity. The Newcastle-Ottawa Scale (NOS) was used to assess the methodological quality of each included study, and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) method was adopted to evaluate the quality of evidence. Result Thirteen studies including 40,868 patients were included, among which 12,086 patients received AF ablation. Meta-analysis indicated that patients with AF ablation had a lower risk of dementia incidence in comparison to patients with AF without ablation [hazard ratio (HR): 0.60, 95% CI: 0.43 to 0.84, p = 0.003 I2 = 40%]. Significant differences were observed in the incidence of new-onset dementia [risk ratio (RR): 0.43, 95% CI: 0.28 to 0.65, p < 0.0001 I2 = 84%]; the changes in the Montreal Cognitive Assessment (MoCA) score [weighted mean difference (WMD): 1.00, 95% CI: 0.36 to 1.64, p < 0.005 I2 = 0%] and Mini-Mental State Examination (MMSE) score (WMD: 0.98, 95% CI: 0.69 to 1.26, p < 0.00001 I2 = 0%]. However, in subgroup analysis, we did not observe significant changes in MoCA score at < 3 months (WMD: 1.20, 95% CI: −0.19 to 2.58, p = 0.09 I2 = 50%) and changes in cognitive function scores between the radiofrequency group and cryoballoon group [standard mean difference (SMD): 0.39, 95% CI: −0.47 to 1.24, p = 0.38 I2 = 87%]. The NOS indicated that included studies were moderate to high quality, while the quality of evidence assessed by GRADE was low in 2 and very low in 2. Conclusion We analyzed the related cognitive outcomes after AF ablation. In the overall population, AF ablation had a positive trend for improving cognitive function at >3 months post-procedure. However, AF ablation might not be related to the improvement of cognitive function at < 3 months. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42021285198.